2019
DOI: 10.1002/maco.201910934
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of anodized AA‐6060 depending on the anodizing bath aging

Abstract: The present work is concerned with the corrosion behavior of anodized AA‐6060 in chloride containing solutions. The anodic layers were produced with identical anodizing parameters but in an anodizing bath at different stages of bath aging or the time of use, respectively. The bath aging was monitored by the conductivity and was related to the consumed charge. The oxide layers were characterized by scanning electron microscopy (SEM)/electron dispersive x‐ray spectroscopy (EDX) and X‐ray fluorescence analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The presence of SiO 2 in the XPS spectra of the O 1s orbital, whose binding energy is between 531.28 and 533.59 eV, Figure 6a'-d', can be attributed to different reasons such as: mechanical polishing, impurity in the anodizing bath or the sealing solution. In some works, different species have been found in the oxides produced by the anodizing process from aged baths; however, this difference was not significant in these works [40].…”
Section: Xps Surface Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…The presence of SiO 2 in the XPS spectra of the O 1s orbital, whose binding energy is between 531.28 and 533.59 eV, Figure 6a'-d', can be attributed to different reasons such as: mechanical polishing, impurity in the anodizing bath or the sealing solution. In some works, different species have been found in the oxides produced by the anodizing process from aged baths; however, this difference was not significant in these works [40].…”
Section: Xps Surface Analysismentioning
confidence: 86%
“…Some authors [17,38,39] have reported that the micrometric scale defects present on the surface of the anodic film have had a similar behavior in the AA2099 alloy due to the high copper content. Figure 1c,d shows samples S3 and S4 with some imperfections (cavity) on the surface; this may be due to varying the current density, the sealing solutions and the preferential dissolution of intermetallic phases, during the growth of the Al 2 O 3 layer in the H 2 SO 4 bath, resulting in a no-uniform surface [40]. Figure 2 shows the micrographs obtained by scanning electron microscope using a backscattered electrons (BSE) detector for cross section anodized samples and their average thickness of the anodic oxide film.…”
Section: Sem Microstructural Analysismentioning
confidence: 99%
“…[ 4,5 ] However, iron and manganese are also present in comparable concentrations in alloys based on primary aluminum and thus no additional measures have to be taken. [ 6 ] In older publications, very high copper levels were pointed out as a FFC‐promoting element: Samples with slightly increased Cu concentration were not studied at that time. [ 7,8 ] In more recent work with alloys containing Cu up to 0.09 wt% it was shown that its effect is indiscernible for levels within the current EN 573‐3.…”
Section: Introductionmentioning
confidence: 99%